Challenging Hegemonic Masculinity: Redefining Heroism in Gene Luen Yang’s The Shadow Hero - E. Anni Selva Iniba; Dr. A. Josephine Alangara Betsy (The Bioscan, 2024)
The superhero genre has long upheld hypermasculine, White-coded ideals that equate heroism with physical dominance, emotional restraint, and social authority. Such portrayals marginalise alternative masculinities and exclude racialised men from heroic representation. Gene Luen Yang’s The Shadow Hero (2014) disrupts these conventions by reimagining the Green Turtle as Hank Chu, a Chinese American superhero negotiating the competing demands of immigrant family expectations, cultural traditions, and societal constructions of masculinity. Drawing on Raewyn Connell’s theory of hegemonic masculinity, this paper examines how Hank’s narrative both reflects and resists dominant masculine archetypes. Through its critique of violence, emotional suppression, and White-coded standards of heroism, the text redefines masculinity by foregrounding compassion, ethical responsibility, and cultural hybridity. By positioning an Asian American protagonist within a genre historically dominated by White hypermasculinity, Yang challenges racialised exclusions and opens space for counter-hegemonic masculinities. The study demonstrates how The Shadow Hero intervenes in broader cultural narratives of gender, race, and power, offering a reimagined model of heroism.